DETERMINAN PEMILIHAN ALAT KONTRASEPSI IUD DI DESA TANJUNGBARU KABUPATEN BEKASI TAHUN 2014 - Dumilah, Retno (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Result of population census in 2010 recorded 237,6 million people is the proof of Indonesia population growth of the projected 5 years earlier than the central bureau of statistics so that the government is trying to reduce the population of the national family planning back from program which has been neglected. This effort was implemented through increasing the use of long period contraceptives methods (MKJP) among others IUD. But the demographic health survey of Indonesia result during the period 1991 until 2007 showed that MKJP especially IUD was decreasing. The district health profile report shows that in 2012 Technical Services Unit Department of Cipayung Primary Health Care in East Cikarang Bekasi working area, Tanjungbaru is a village who has a lowest achievement of IUD contraceptive acceptors.This research is a cases control research with fertile-age couples acceptors IUD as a group of cases and fertile-age couples acceptors besides IUD as the control group. The population in this research was fertile-age couples in the Tanjungbaru village area which totaled 5.297 couples who then selected in a stratified random sampling (random stratification) covering 98 fertile-age couples.The source of the primary data was questionnaire and the the source of the secondary data was the scope of family planning monitoring of Technical Services Unit Department of Cipayung Primary Health Care in East Cikarang Bekasi in 2013. Statistical analysis was performed with Chi square test.The analysis results showed that there were no significant differences between predisposing factors (including age, education, occupation, knowledge and parity) with the selection of IUD contraseptive (p>0,05) but there was significant difference between enabling factor (source of information) and reinforcing factor (husband’s support) with the selection of IUD contraseptive (p<0,05).Conclusions: there are a correlation between source of information and husband’s support with the selection of IUD contraceptive so that needed the evaluation of the program related to the process of counseling in order to identify things were controlling and involvement of husband at a time do IUD family planning counseling.Keywords:predisposing factors, enabling factor, reinforcing factor, the selection of IUD contraseptive.